2015
DOI: 10.1186/s12944-015-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

The apoB100/apoAI ratio is independently associated with the severity of coronary heart disease: a cross sectional study in patients undergoing coronary angiography

Abstract: BackgroundLipoprotein ratios have been shown to be associated with the occurrence of coronary heart disease (CHD), but little is known about their relationships with the severity of CHD.MethodsA total of 792 angiographically defined CHD patients were enrolled following their admission. Patients were stratified into three groups based on the tertile of the Gensini scores (≤33rd percentile, 33rd to 66th percentile and ≥66th percentile) or the number of stenotic coronary branches (single-branch stenosis, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
(27 reference statements)
1
22
2
1
Order By: Relevance
“…29 In two studies evaluating Gensini score and LDL-C relationship, LDL-C showed no significant difference when compared to high and low Gensini scores. 30 , 31 In our study, LDL-C was not correlated to Gensini or SYNTAX scores. Non-HDL-C was found to be higher in patients with a Gensini score of 50 or greater than patients with a Gensini score of less than 50.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…29 In two studies evaluating Gensini score and LDL-C relationship, LDL-C showed no significant difference when compared to high and low Gensini scores. 30 , 31 In our study, LDL-C was not correlated to Gensini or SYNTAX scores. Non-HDL-C was found to be higher in patients with a Gensini score of 50 or greater than patients with a Gensini score of less than 50.…”
Section: Discussioncontrasting
confidence: 57%
“…29 Em dois estudos que avaliaram a relação entre escore Gensini e LDL, o LDL-C não teve diferença significativa quando comparado aos escores alto e baixo de Gensini. 30 , 31 Em nosso estudo, o nível de LDL não se correlacionou com os escores Gensini ou SYNTAX. Verificou-se que o não-HDL não era maior em pacientes com escore Gensini igual ou superior a 50 em comparação a pacientes com escore Gensini inferior a 50.…”
Section: Discussionunclassified
“…Dyslipidemia is viewed as a necessary condition for atherosclerosis, and studies have shown that dyslipidemia may account for 50% of the attributable risk in patients with CAD. Therefore, recent studies on the correlation between lipid biomarkers and coronary heart disease have become the focus 21 . HDL-C, as a typical lipid related biomarker, plays an important protective role in the process of atherosclerosis and in ammation due to its anti-oxidant, anti-in ammatory, anti-apoptotic and anti-thrombotic properties [22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…The apo B/apo A1 ratio is a typical marker for the atherogenic /antiatherogenic condition, and a higher apo B/apo A1 ratio represents progression in the atherosclerotic state. Previous studies have suggested that a high apo B/apo A1 ratio strongly correlates with pathophysiological markers of atherosclerosis defined by coronary angiography [ 8 , 20 ], and calcium scores of the coronary arteries [ 21 ], and by ultrasound techniques such as the thickness of carotid arteries [ 16 , 22 , 23 ], endothelial dysfunction [ 24 ] and existence of femoral plaques [ 25 ]. In addition, a high apo B/apo A1 ratio can also be used to predict risk of carotid plaque development [ 26 ] and major adverse cardiovascular events [ 14 , 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that, lipid-transporting apolipoprotein is an essential structural component of the lipoprotein cholesterol [ 6 ], VLDL, IDL and LDL cholesterol can each carry only a single apolipoprotein B (apo B) [ 7 ] and this characteristic can be used to reliably reflected the number of atherogenic lipoproteins in the plasma. In contrast, apo A1 has a strong association with HDL levels and accounts for approximately 60-70% of the total apolipoproteins in HDL-C, the plasma content of apo A1 represents the total of antiatherogenic particles [ 8 ]. Therefore, the ratio of apo B to apo A1 (apo B/apo A1) reflects the balance of proatherogenic and antiatherogenic particles.…”
Section: Introductionmentioning
confidence: 99%